KAJIAN RESPON PETANI TERHADAP BUDIDAYA TEMBAKAU DAN PASCA PANEN DI KABUPATEN SIDOARJO - Djoko Soejono (University of Jember, 2012)
The overall aim is to develop people's tobacco cultivation as one of the potential commodities in Sidoarjo. Specific objectives are (1) to determine the response of farmers to the cultivation and post-harvest tobacco, (2) to analyze the socioeconomic factors that affect the response of farmers to the cultivation and post harvest tobacco, and (3) to develop strategies to increase the interest of farmers to develop farming and post harvest tobacco Location determined by the method of study purposive/deliberate on the basis that Sidoarjo is a developing area of ​​tobacco plants . Required data types can be distinguished on the primary data and secondary data. Studies using comparative descriptive survey method approach and Quantitative . Primary data collection with incidental sampling method, and the third data collection that has been processed by the field work of each surveyor. Analysis tools are used (1) Analysis of Motivation, (2) regression analysis, (3) Analysis of FFA (Field Force Analysis). The conclusions of the study are (1) tobacco farmers in Sidoarjo tobacco farming activities on the basis of his business needs which include physiological needs, safety needs, social needs, esteem needs and self-actualization needs. The fifth requirement of physiological needs is the primary goal of farmers who grew tobacco, where the revenue generated from tobacco farming used to meet personal and family needs of farmers, (2) Social and economic factors affecting the response of farmers in getting tobacco in Sidoarjo regency is the number of seeds and the selling price of tobacco in the form of dry, while a variable number of dependents, distance of land and the production does not affect the response of tobacco farmers seek in Sidoarjo, and (3) driving factor in improving the response of farmers seeking tobacco, both of cultivation and post-harvest aspects is the government assistance programs, while weak business partnership is the limiting factor. Keyword : tobacco, post-harvest, farmers response